1999
DOI: 10.1016/s1010-7940(99)00246-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caffeic acid phenethyl ester (CAPE) on spinal cord ischemia/reperfusion injury in rabbits

Abstract: These results suggest that CAPE may be an available agent to protect the spinal cord from ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 21 publications
5
133
3
3
Order By: Relevance
“…[17] The protective effects of CAPE have been practiced in various studies dealing with cerebral ischemia-reperfusion injury, spinal cord ischemia-reperfusion injury, Parkinson's disease, hypoxic ischemic brain damage in newborns, multiple sclerosis, convulsions, brain tumors, toxic effects of therapeutic agent in anticancer therapies, and hepatic encephalopathy. [3][4][5][6][7][8][9][10][11] There are only five studies in the literature evaluating the effects of CAPE in the spinal cord. [5,8,11,18,19] Two of these studies have been performed to evaluate the protective effects of CAPE against experimental allergic encephalomyelitisinduced oxidative stress, and in methotrexate administered rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] The protective effects of CAPE have been practiced in various studies dealing with cerebral ischemia-reperfusion injury, spinal cord ischemia-reperfusion injury, Parkinson's disease, hypoxic ischemic brain damage in newborns, multiple sclerosis, convulsions, brain tumors, toxic effects of therapeutic agent in anticancer therapies, and hepatic encephalopathy. [3][4][5][6][7][8][9][10][11] There are only five studies in the literature evaluating the effects of CAPE in the spinal cord. [5,8,11,18,19] Two of these studies have been performed to evaluate the protective effects of CAPE against experimental allergic encephalomyelitisinduced oxidative stress, and in methotrexate administered rats.…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of CAPE in the nervous system have been reported in cerebral ischemic reperfusion injury, ischemic damage of the spinal cord, Parkinson's disease, convulsions, multiple sclerosis, brain tumors, hepatic encephalopathy, and against toxic effects of therapeutic agents in anticancer therapy. [3][4][5][6][7][8][9][10][11] Moreover, studies evaluating its protective effect in spinal cord ischemia-reperfusion models and hemi-transection model have been reported; however, there is no study investigating the acute effects of CAPE in traumatic acute spinal cord injury in clip compression model. Therefore, this study was conducted to evaluate the early anti-cytotoxic effects of CAPE in acute spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated to be a specific inhibitor of activation of nuclear transcript factor NF-B (2,3). Previous studies have shown that this compound could protect the spinal cord and brain from ischemia reperfusion injury (4,5) and prevent neurotoxic events caused by excessive inflammatory reaction in brain (6). Several lines of evidence also indicate that CAPE may modify the redox state in transformed fibroblast cells and in leukemic HL-60 cells (7)(8)(9).…”
Section: Caffeic Acid Phenethyl Ester (Cape)mentioning
confidence: 99%
“…Spinal cord I-R injury is a persistent clinical problem in surgical repair of thoracic and thoracoabdominal aneurism surgeries 19,20 . The major cause of spinal cord injury, during and after aortic surgery to the occurrence of one or more of the three following events: (I) the duration and degree of ischaemia; (II) failure to re-establish blood flow to the spinal cord after repair; (III) a biochemically mediated reperfusion injury 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response with production of cytokines by microglia and activated neutrophils also contributes to generation of these radicals 23,24 .…”
Section: Discussionmentioning
confidence: 99%